Perceived parental warmth and depression in early adolescents: path analysis on the role of self-esteem as a mediator - Lim, Hui Jun; Baharudin, Rozumah; Tan, Jo Pei (Universiti Putra Malaysia Press, 2013)
The prevalence of depression in Malaysia instigated the twofold objectives of the present study. First, the relationship between perceived parental warmth, self-esteem and depression was examined, followed by the exploration on the role of self-esteem as a mediator between perceived parental warmth and depression among early adolescents. The model for early adolescent's depression was guided by Beck's cognitive theory of depression and parental acceptance-rejection theory. A total of 1394 adolescents aged 13 to 15 years, who reported living with both married and biological parents, provided complete self-report data on the measures (Conger's subscale for parental warmth, Rosenberg Self-esteem Scale, Beck Depression Inventory for Malays) for the three observed variables (namely, perceived parental warmth, self-esteem and depression). In order to determine the role of self-esteem as a mediator, Pearson correlation was first conducted to ensure that the initial variable (perceived parental warmth) was related to the outcome (depression) and mediator (self-esteem) variable as suggested by Baron and Kenny (1986). Path analysis was then employed to establish the mediating effect of self-esteem. Results revealed that the data from the study fitted the model and that perceived parental warmth had an indirect effect on depression through self-esteem. Findings also revealed that self-esteem was a complete mediator in the relationship between perceived parental warmth and depression. Implications for the alternative approach in preventing depression were further discussed.